20 Years of Olympic Media Research: Trends and Future Directions - Geurin, Andrea N.; Naraine, Michael L. (Frontiers in Sports and Active Living, 2020)
The Olympic Games is the largest multisport event in the world, regularly drawing global audiences in the billions to watch coverage of athletes from hundreds of nations. It has received a great deal of scholarly attention, especially in terms of media coverage, consumption, and co-creation. As coverage has the ability to impact media consumers' perceptions of nations, cultures, and issues, it is important to develop an understanding of research trends relating to the Olympic Games and media in order to uncover gaps in the literature which may be filled by future scholarly work. Therefore, in order to highlight trends in the established literature and uncover areas for development, a systematic literature review was conducted to examine the state of Olympic media research over a 20-year time period (1999–2018). A total of 221 articles were examined, revealing insights into the types of research being produced from theoretical, methodological, and contextual perspectives. Results revealed a significant proportion of scholarship focused on the Summer Olympic Games, the United States, newspaper accounts of the Games, and utilized media framing and agenda setting frameworks and the content analysis methodology. Just over half of the studies utilized a theoretical or conceptual framework, the prevalence of which increased over time. Core areas for continued development in the Olympic media space include embracing and grounding research in theory, diversification in research context, and expanding upon the definition of the Olympic Games within the greater Olympic Movement.